2022
DOI: 10.1002/adfm.202210194
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Polarization in the Ferroelectric Electrocatalysts to Boost Water Electrolysis

Abstract: Water splitting is the most important process for making green hydrogen. The positive effects of ferroelectric polarization in various kinds of water splitting are well recognized, but the study of electrocatalytic water splitting is still in its infancy. Herein, a family of intrinsic ferroelectrics with a flexible tetragonal tungsten bronze structure is chosen to accommodate oxygen evolution reaction (OER) active sites together with its freedom for tuning the ferroelectric polarization. It is found that the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Furthermore, when comparing the j CST -poling voltage curve with the j WO -poling voltage curve in Figure a, it indicates that the surface reaction kinetics have also been affected by the external poling. Actually, it has been reported that the poling can dramatically alter the electrolysis kinetics of ferroelectric electrocatalysts. , Our result also found that the surface reaction efficiency (η rea ) is affected by the external poling (Figure S6). Herein, we will focus majorly on the influence of poling on the charge separation and transfer process, which has been less experimentally investigated.…”
Section: Resultssupporting
confidence: 68%
“…Furthermore, when comparing the j CST -poling voltage curve with the j WO -poling voltage curve in Figure a, it indicates that the surface reaction kinetics have also been affected by the external poling. Actually, it has been reported that the poling can dramatically alter the electrolysis kinetics of ferroelectric electrocatalysts. , Our result also found that the surface reaction efficiency (η rea ) is affected by the external poling (Figure S6). Herein, we will focus majorly on the influence of poling on the charge separation and transfer process, which has been less experimentally investigated.…”
Section: Resultssupporting
confidence: 68%
“…Therefore, the ferroelectric characteristics of the prepared Mn_NiO and NiO were evaluated using polarization hysteresis loop measurements. Figure c displays the effect of Mn doping in the shape of the polarization–electric field hysteresis loops ( P – E loops), the amount of remnant polarization ( P r ), and the saturation polarization ( P s ) . Mn_NiO reveals higher P r and P s values (10.32 and 10.02 μC·cm –2 ) under the electric field of −2 to 2 kV cm –1 , higher than those of NiO (8.72 and 8.74 μC·cm –2 ), which demonstrates the increased surface polarization with Mn doping in NiO.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4c displays the effect of Mn doping in the shape of the polarization−electric field hysteresis loops (P−E loops), the amount of remnant polarization (P r ), and the saturation polarization (P s ). 63 Mn_NiO reveals higher P r and P s values (10.32 and 10.02 μC•cm −2 ) under the electric field of −2 to 2 kV cm −1 , higher than those of NiO (8.72 and 8.74 μC• cm −2 ), which demonstrates the increased surface polarization with Mn doping in NiO. Moreover, the surface dipole moment along vectors u and v in (0 1 1) is calculated (Figure 4d), where both the dipole moments along vectors u and v in Mn_NiO are distinctly increased, further confirming the origin of the enhanced hydrophilicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…38 A similar phenomenon was observed in bismuth ferrite systems, where three different phases, perovskite BiFeO 3 , mullite Bi 2 Fe 4 O 9 , and sillenite Bi 25 FeO 40 , all display enhanced electrochemical activity after being positively poled, reported by Vaidya et al 39 A recent work based on a tetragonal tungsten bronze (TTB)-structured Sr 0.5 Ba 0.5 Nb 2 O 6-δ (SBN) doped by Co or filled by K elements demonstrated the effect of polarization magnitude on OER efficiency, where K-filled SBN with stronger polarization exhibited a smaller overpotential than Co-doped SBN with a weaker polarization. 40 These studies have revealed the advantages of utilizing ferroelectric polarization to boost water electrolysis. However, the observed electrochemical current density in most cases is much lower than that in common electrocatalysts, ascribed to their semiconducting characteristic.…”
Section: Introductionmentioning
confidence: 99%